Speaking up for Others : Locus Standi and Representative Bodies - Bowal, Peter (Les Cahiers de droit, 1994)
This article addresses the issue of whether a representative body such as a trade association would, in the ordinary course, enjoy standing to present a public law question to the court on behalf of one or more of its members where there is no more compelling demand for representative advocacy other than the interests of convenience or public relations. The author canvasses recent case law in Canada and concludes that it tends to a marked restriction in public interest access to the courts. The success in obtaining standing would depend on a number of factors including the manner of conduct of the litigation, the political nature of the subject matter and, increasingly, the workload of the court.